Semi-Free Buffet Stalls in East Java: An Islamic Economic Analysis of Food Security and Cultural Poverty Risk - Hasyim, Muhammad Sulaiman; Riyadi, Abdul Kadir; Syafa'ah, Mamik (El-Qist: Journal of Islamic Economics and Business (JIEB), 2025)
This study investigates the emerging phenomenon of “semi-free buffet stalls” (warung semi-gratis) in East Java, Indonesia—community-based initiatives that provide food on an eat-as-you-wish, pay-as-you-can basis. While these stalls contribute to food security among low-income families, they may paradoxically reinforce dependency and cultural poverty. Addressing the research gap in Islamic economic perspectives on these dual functions, this study employs a qualitative descriptive approach, combining literature review, media content analysis, and comparative analysis of national and international studies. The findings reveal that, although semi-free stalls alleviate immediate economic pressures, passive consumption without participatory reciprocity can foster dependency and learned helplessness. Nevertheless, when integrated with empowerment-oriented programs grounded in al-Ta‘āwun (cooperation)—such as voluntary contributions, skill development, and collective work—these initiatives can balance generosity with capacity building. This research contributes to Islamic economics by proposing a hybrid model of charitable and transformative food distribution, offering a framework for inclusive social finance practices applicable to other Muslim-majority and developing contexts.